Using Information Communication Technologies to Foster the Communicative Competence in Undergraduate Students at the UPTC - Camargo Pongutá, David (Universidad Pedagógica y Tecnológica de Colombia, 2018)
This research article describes the results of implementing activities through Information Communication Technologies (ICTs)  in order to foster the communicative competence in a group of students at Universidad Pedagógica y Tecnológica de Colombia, a public University in Sogamoso, Boyacá.  After an exploration in which it was determined that students prefer activities with ICTs to learn English, contents and activities were adapted so they could fit students’ interests. The results are shown in three categories: ICTs as a tool to foster oral production, ICTs to build vocabulary, and ICTs as a motivator to learn and interact in the target language.